Tourism and visual culture, theories and concepts - Burns, Peter; Palmer, Cathy.; Lester, Jo-Anne. (CAB International, 2010)
This book explores, in various ways, the relationship between tourism and visuality. In so doing, the 17 chapters contribute to what has become a growing interest and body of knowledge defining the contours of the visual culture of tourism. What emerge as important themes in the conceptualization of tourism and visuality are nostalgia, the ways in which photographic images act as a mediating element in prefiguring perceptions, the sentimentality of landscapes, the conception and use of space (i.e. space as a social construct), and the negative consequences of the tourist gaze.